Dual gas diffusion cathode design for microbial fuel cell (MFC): optimizing the suitable mode of operation in terms of bioelectrochemical and bioelectro‐kinetic evaluation. Issue 3 (13th January 2015) - Pasupuleti, Suresh Babu; Srikanth, Sandipam; Dominguez‐Benetton, Xochitl; Mohan, S Venkata; Pant, Deepak
Abstract: BACKGROUND: Upscaling microbial fuel cells (MFCs) to make them energy‐competitive systems requires a systematic understanding of their operating conditions. This study emphasizes the operation of a new MFC design with two gas diffusion cathodes under three different operational modes (batch mode (MFC‐BM), semi‐continuous mode (MFC‐SCM) and continuous mode (MFC‐CM)), towards increasing the power density, substrate utilization, bioelectrochemical kinetics and energy conversion efficiencies. RESULTS: Higher power density was recorded with MFC‐SCM (20.54 mW m −2 ) followed by MFC‐CM (17.22 mW m −2 ) and MFC‐BM (0.75 mW m −2 ). Such power density magnitudes were obtained with high anode projected surface area 220 cm 2, which is about 10–100 times larger than frequently used in laboratory‐scale MFCs. On the contrary, susbtrate utilization was higher with MFC‐BM (91–96%) followed by MFC‐SCM (74–84%) and MFC‐CM (53–81%). A higher coulombic efficiency (CE) was obtained with the MFC‐CM (7.5–11.2%), followed by MFC‐SCM (5.4–5.6%) and MFC‐BM (0.5–4%). This is of interest due to its dependence on both current generation as well as substrate utilization. Cyclic voltammograms along with derived bioelectro‐kinetic parameters, i.e. redox Tafel's slopes ( βa / βc ) and electron transfer co‐efficients ( αa / αc ), also explained the higher performance of MFC‐CM and MFC‐SCM. CONCLUSION: Output from this study demonstrates clearly that the new MFC design can be effectively operated under continuous mode operation with high retention time to enhance wastewater treatment along with good amounts of power output. © 2014 Society of Chemical Industry